ON THE DYNAMIC REQUESTS - Minodora-Maria PASARE; Catalina IANASI (Fiabilitate şi Durabilitate)
The study of machine parts movements required by inertial forces is actually a dynamic problem. The machine parts in motion are under dynamic stress due to the inertial forces that appear and overlap the directly applied forces and also connection forces. In the paper, the movements that are studied from a dynamic point of view are those that involve acceleration.